Effect of arrangement factors on the optical properties of ZnO thin films by chemical vapor deposition - Mikhail Essa Mansour; Yasir Hussein Mohamed (College of Education for Pure Sciences, 2010)
ABSTRACT: Highly transparent ZnO thin films were grown by chemical vapor deposition (CVD) on glass substrates at various substrate temperatures and sample positions inside the deposition chamber. The optical properties of the films were investigated. Optimized ZnO films have an average transmission in the visible range is about 90% at substrate temperature 500 ºC and the optical energy gap is 3.2 eV. It was also found that the best position of the films inside the chamber is about 16 cm from the inlet side of the gases.